Demographics, Disease Characteristics, and Time to Effective Treatment of Patients with Psoriasis in the Ghent PsoPlus Cohort of 2021 - Evelyn Meulewaeter; Anke Eylenbosch; Evelien Verhaeghe; Rani Soenen; Jo Lambert (Adis, Springer Healthcare, 2024)
Abstract Introduction Psoriasis is a chronic immune-mediated skin disease with several comorbidities and a considerable influence on quality of life. Many patients with moderate-to-severe psoriasis are undertreated and have a substantial disease duration before effective treatment is started. This study analyzed patient and disease characteristics and time to effective treatment of patients with psoriasis who consulted PsoPlus. It also examined whether a treat-to-target (T2T) approach, which is implemented in PsoPlus, has an impact on treatment choice and disease progression. Methods Through a single center, retrospective study, 170 patients in the PsoPlus dedicated clinic were compared at moment of enrollment in PsoPlus and at the last recorded consultation in 2021. Results Median disease duration at the first PsoPlus consultation was 16.0 (interquartile range (IQR) 19.0) years. There was a significant difference in Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) between the first and the last recorded PsoPlus consultation (PASI 6.0 (IQR 6.4) vs. 0.6 (IQR 2.6); DLQI 11 (IQR 11) vs. 2 (IQR 6); p < 0.001). A weak positive Spearman correlation (r s) was found between disease duration and PASI at the first PsoPlus consultation (r s = 0.175; p = 0.034), while a weak negative correlation (r s = − 0.2; p = 0.013) was found at the last registered PsoPlus consultation. Patients with a disease duration of more than 20 years had significantly more switches of treatment than those with a shorter disease duration (p < 0.001). Median time from psoriasis onset until PASI ≤ 2 was 16.0 years. Median time from the first PsoPlus consultation until PASI ≤ 2 was 7.0 months. Conclusion The PsoPlus program with its T2T approach effectively improves clinical outcomes and quality of life for patients with psoriasis in a relatively short period, emphasizing the value of a structured, personalized treatment plan for long-term management.